ANALISA GAYA MENGAJAR GURU EKONOMI DI SMA NEGERI SE-KECAMATAN LAHAT - Muhammad Safari; Riswan Jaenudin; Dewi Koryati (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2014)
This research entitled Analysis Teaching Style Teachers Economics in SMA Negeri Se-Subdistrict Lahat. The formulation of the problem in research is how to teach style of economics teacher in SMA Negeri Se-Kecamatan Lahat. The method used is descriptive quantitative. Variable in research is teacher teaching style. The teaching styles studied are classical teaching style, technological, personalization and interconnection teaching style. The population in this study were all teachers of economics in Lahat Sub-district with 17 teachers. The sample selection was taken by using purposive sampling technique with 7 teachers. Data collection techniques used in this study are observation and interview. Observations and interviews were used to collect data on teachers' teaching styles. From the research results show that teaching style is often used is as follows, 1) interactional teaching style with an average of 75.08%, 2) teaching style personalization with an average of 73.60%, 3) technological teaching style with the average of 64.20%, and 4) classical teaching style with an average of 48.52%. In addition, in this study also found that the factors that influence the style of teaching of economic teachers in SMA Negeri Se-Kecamatan Lahat influenced by the teacher's working period and school infrastructure advice. The suggestion of this research result is that teacher and school side can improve their knowledge and teaching skill so that the learning process can run better.